Programming high-speed running and mechanical work in relation to technical contents and match schedule in professional soccer - Buchheit, M. (Sport Performance & Science Reports, 2019)
As previously emphasized (1), the management of highspeed running (HSR) forms a vital training program puzzle piece we need to consider from both a performance and injury mitigation perspective. Regular HSR supplementation helps maintain a stable HSR load (1), which indirectly limits the occurrence of spikes and in turn, may lower injury risk (2). Beyond only performing high-intensity interval training (HIIT, generally run around 18-22 km/h), sprinting maximally (3) or at least reaching velocities close to maximal velocity (4) is also required to cover the full HSR velocity range. In fact, while many fear the implementation of maximal sprinting during practice to avoid acute muscular strain, the reality is that sprinting itself is likely more the solution versus the problem (3). Typical strengthening exercises are unlikely intense enough to replicate sprint demands (i.e., <75% of the EMG activity reached during sprinting (5)). This suggests that sprint-specific neuromuscular demands are unique and can`t be replaced by any other (isolated) muscular actions (3). While the management of HSR may essentially protect the integrity of the hamstrings, the importance of mechanical work (MW, accelerations, decelerations and changes of direction) programming and supplementation should also not be overlooked with respect to other important muscles groups (i.e., quads, gluts and adductors). Of course, all this is easier said than done, with the actual programming of such specific locomotor loads requiring particular attention in relation to typical soccer training contents, match demands and timing. In this short opinion piece, I offer some guidelines that coaches and practitioners can use to appropriately program HSR and MW sequences in relation to technical training contents and match schedules (i.e., different weekly microcycles).